2017
DOI: 10.1016/j.omtn.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Locked Nucleic Acid Gapmers and Conjugates Potently Silence ADAM33, an Asthma-Associated Metalloprotease with Nuclear-Localized mRNA

Abstract: Two mechanisms dominate the clinical pipeline for oligonucleotide-based gene silencing, namely, the antisense approach that recruits RNase H to cleave target RNA and the RNAi approach that recruits the RISC complex to cleave target RNA. Multiple chemical designs can be used to elicit each pathway. We compare the silencing of the asthma susceptibility gene ADAM33 in MRC-5 lung fibroblasts using four classes of gene silencing agents, two that use each mechanism: traditional duplex small interfering RNAs (siRNAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…No significant silencing effect was observed at low concentration (1 μM) without transfection agent. This could be a result of the reported slow and less efficient unassisted gymnotic intracellular delivery of gapmers that requires a relatively high concentration . Accordingly, at a relatively high concentration (10 μM), high levels of HER3 gene silencing effects were observed in both PC‐3 and Caco‐2 cell lines without transfection agent.…”
Section: Discussionmentioning
confidence: 99%
“…No significant silencing effect was observed at low concentration (1 μM) without transfection agent. This could be a result of the reported slow and less efficient unassisted gymnotic intracellular delivery of gapmers that requires a relatively high concentration . Accordingly, at a relatively high concentration (10 μM), high levels of HER3 gene silencing effects were observed in both PC‐3 and Caco‐2 cell lines without transfection agent.…”
Section: Discussionmentioning
confidence: 99%
“…LNA phosphoramidites were synthesized from the 3′-hydroxyl precursors (Rasayan) and assembled into oligonucleotides as described previously ( 49 ). ASOs were deprotected using concentrated aqueous ammonia for 16 h at 55°C and were characterized by LCMS ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Single-stranded AONs can bind to and interact with many different target classes. AONs can inhibit miRNA expression [23][24][25], induce alternative splicing [26][27][28][29][30][31], and inhibit mRNA expression by both a steric block [32,33], and an RNase recruiting mechanism [34,35]. Except for miRNA inhibition, it has been shown that AON activity is most effective in the nucleus [36], and in applications involving splice modulation, nuclear entry of AONs is crucial.…”
Section: Introductionmentioning
confidence: 99%